2021
DOI: 10.1002/jcla.24106
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TUG1 upregulates VEGFA to enhance malignant behaviors in stomach adenocarcinoma by sponging miR‐29c‐3p

Abstract: Background Long noncoding RNA (lncRNA) TUG1 has been reported to display a pivotal role in the tumorigenesis and malignant progression of various types of cancers, including stomach adenocarcinoma (STAD). However, the contribution of aberrant expression of TUG1 and the mechanism by which it serves as a competing endogenous RNA (ceRNA) in STAD remains largely obscure. Methods The human STAD cell lines (MGC‐803 and AGS), human normal gastric epithelial cell line (GES‐1), human umbilical vein endothelial cells (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Cur-rently, a lot of research has authenticated that LncRNA TUG1 influences the malignant behavior of tumors by inhibiting miRNAs [3,4]. For instance, LncRNA TUG1 can adsorb miR-29c-3p, which enhances the malignant behavior of gastric adenocarcinoma [5]. Yao et al have found that knockout of LncRNA TUG1 can inhibit viability, CM, and differentiation and lead to CA of osteoblasts in patients with maxillary fractures, suggesting that LncRNA TUG1 is also involved in the biological process of osteoblast CP and CA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cur-rently, a lot of research has authenticated that LncRNA TUG1 influences the malignant behavior of tumors by inhibiting miRNAs [3,4]. For instance, LncRNA TUG1 can adsorb miR-29c-3p, which enhances the malignant behavior of gastric adenocarcinoma [5]. Yao et al have found that knockout of LncRNA TUG1 can inhibit viability, CM, and differentiation and lead to CA of osteoblasts in patients with maxillary fractures, suggesting that LncRNA TUG1 is also involved in the biological process of osteoblast CP and CA [6].…”
Section: Introductionmentioning
confidence: 99%
“…RP11−834C11.4 together with other lncRNAs acted as risk factors in colon cancer [ 34 , 35 ]. TUG1 played important role in the development or progression of hepatocellular carcinoma [ 36 ], stomach adenocarcinoma [ 37 ] and Bladder Cancer [ 38 ]. MGC12916, NCRNA00094 and LOC541771 have been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…e lncRNA TUG1 enhances the malignant behavior of gastric adenocarcinoma by regulating miR-29c-3p to upregulate VEGFA [32].…”
Section: Discussionmentioning
confidence: 99%